Legal Protection in Labor Dispute Settlement Through Industrial Relations Mechanism - Shinta Azzahra Sudrajat; Arzam Arzam; Doli Witro (UIN Sunan Gunung Djati, 2022)
This article discusses one of the Indonesian legal products used in the settlement of labor disputes, namely the industrial relations mechanism, which is part of the legal product to resolve disputes by legal protection measures. This article aims to find out the mechanism of Industrial Relations to provide legal protection in labor disputes. This article is normative juridical research that analyzes secondary data from legal studies literature in the form of books, journals, and other materials related to the research topic of this article. The data analysis technique used is content analysis. The results of the analysis show that legal protection in labor disputes with industrial relations mechanisms can be carried out through the Bipartite, Tripartite, and Industrial Relations Courts (PHI). The results of this court's decision do not only stop in writing on paper, but there must be a follow-up from the losing party to carry out their obligations based on the demands that have been set.